2016
DOI: 10.1016/j.pmedr.2016.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Associations between noncommunicable disease risk factors, race, education, and health insurance status among women of reproductive age in Brazil — 2011

Abstract: BackgroundNoncommunicable disease (NCD) risk factors increase the risk of adverse reproductive health outcomes and are becoming increasingly common in Brazil.MethodsWe analyzed VIGITEL 2011 telephone survey data for 13,745 Brazilian women aged 18–44 years in a probabilistic sample from 26 Brazilian state capitals and the Federal District. We examined associations between NCD risk factors (fruit and vegetable intake, leisure time physical activity, alcohol consumption, smoking status, BMI and hypertension statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 39 publications
3
21
0
5
Order By: Relevance
“…The effects of the risk factors derived from our model concur with predictors of the NCDs as noted in other studies [3639]. For instance, there is a significant direct relationship between the number of NCD risk factors with body mass index, systolic blood pressure, but an inverse relationship with consumption of fruit and vegetables.…”
Section: Discussionsupporting
confidence: 86%
“…The effects of the risk factors derived from our model concur with predictors of the NCDs as noted in other studies [3639]. For instance, there is a significant direct relationship between the number of NCD risk factors with body mass index, systolic blood pressure, but an inverse relationship with consumption of fruit and vegetables.…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, few studies address the magnitude of NCDs among women of reproductive age [9][10][11] , since the predominant approach to research on this specific group is related to reproductive issues such as family planning, prenatal care, prevention and screening for gynecological cancers. Research dealing with NCDs shows how much these diseases increasingly affect women [10][11][12] , even though they are young. Consequently, they also affect reproductive issues 13 .…”
Section: Introductionmentioning
confidence: 99%
“…whether women with unfavorable socioeconomic conditions are more susceptible to NCDs and their risk factors. A previous study with the Surveillance of Risk Factors and Protection for Chronic Diseases by Telephone Survey (Vigilância de Fatores de Risco e Proteção para Doenças Crônicas por Inquérito Telefônico -Vigitel) found that women of reproductive age with low levels of education were more inactive, and had higher levels of smoking and hypertension 11 . Cardiovascular diseases are also treated and prevented to a lesser extent among women, especially those who are in positions of social vulnerability 14 .…”
Section: Introductionmentioning
confidence: 99%
“…As the epidemiological transition begins, noncommunicable diseases are starting to replace communicable diseases; however, infectious conditions continue to be highly prevalent in the country. 7,8 In Brazil and other countries, a high burden of noncommunicable diseases exists, accounting for 72% of all deaths. 9 The major causes of death include cardiovascular disease (30.7%), cancer (16.9%), external causes (13.4%), and respiratory disease (11.6%).…”
mentioning
confidence: 99%